2022
DOI: 10.3389/fpsyg.2022.904151
|View full text |Cite
|
Sign up to set email alerts
|

A Structural Model of Teacher Self-Efficacy, Emotion Regulation, and Psychological Wellbeing Among English Teachers

Abstract: Because of the exacting nature of teaching, identifying factors affecting teachers’ mental health and psychological wellbeing are of paramount importance. Parallel with this line of inquiry, the goal of this project was to test a model of psychological wellbeing based on teacher self-efficacy and emotion regulation in an EFL context. To this end, 276 Iranian English teachers participated in this survey. First, the measurement models for the three latent constructs were verified through performing Confirmatory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 83 publications
(116 reference statements)
7
17
0
Order By: Relevance
“…Similarly, Chen (2018) confirmed that teacher efficacy is positively associated with their emotions. This finding is in accord with those of Fathi et al (2020) , Heydarnejad et al (2021a) , Liu H. et al (2021) , and Amirian et al (2022) as well as Xiyun et al (2022) . Additionally, Cansoy et al (2020) and Zheng et al (2022) confirmed that teacher emotional wellbeing and self-efficacy beliefs are interrelated.…”
Section: Discussionsupporting
confidence: 93%
“…Similarly, Chen (2018) confirmed that teacher efficacy is positively associated with their emotions. This finding is in accord with those of Fathi et al (2020) , Heydarnejad et al (2021a) , Liu H. et al (2021) , and Amirian et al (2022) as well as Xiyun et al (2022) . Additionally, Cansoy et al (2020) and Zheng et al (2022) confirmed that teacher emotional wellbeing and self-efficacy beliefs are interrelated.…”
Section: Discussionsupporting
confidence: 93%
“…That is to say, the levels of teacher efficacy positively correlate with increased ER among EFL university professors. This result corroborates with those of Heydarnejad et al (2021a) and Xiyun et al (2022) , as well as Fathi et al (2020) . Moreover, the findings from Zee and Koomen (2016) and Cansoy et al (2020) evinced that teacher self-efficacy and their psychological wellbeing are interwoven.…”
Section: Discussionsupporting
confidence: 92%
“…The negative relationship between ER and burnout was also confirmed by this study. Parallel with this line of inquiry, the mediator roles of teacher self-efficacy and ER on psychological wellbeing in an EFL context was concluded ( Xiyun et al, 2022 ).…”
Section: Literature Reviewmentioning
confidence: 95%
See 1 more Smart Citation
“…The study was conducted in a stratified random sample of 353 undergraduates in 4 years from 2 comprehensive universities in Beijing ( Manasia and Macovei, 2020 ). In one study, a stratified random sample of 353 undergraduates in 4 years was selected from two comprehensive universities in Beijing, and the study showed that there was a significant correlation between college students’ achievement motivation and subjective well-being index ( Xiyun et al, 2022 ).…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%